Prenatal Diagnosis of Fetal Encephalomalacia after Maternal Diabetic Ketoacidosis - Love, Rozalyn; Lee, Amy; Matiasek, April; Carter, William; Ylagan, Marissa (American Journal of Perinatology Reports, 2014)
Introduction Encephalomalacia in a developing fetus is a rare and devastating neurological finding on radiologic imaging. Maternal diabetic ketoacidosis (DKA) can lead to metabolic and vascular derangements which can cause fetal encephalomalacia.Case We report the case of a 27-year-old pregnant woman with White's Class C diabetes mellitus who presented in the 25th week of gestation with DKA. Four weeks after her discharge, marked fetal cerebral ventriculomegaly was noted on ultrasound. A subsequent fetal magnetic resonance imaging (MRI) demonstrated extensive, symmetric cystic encephalomalacia, primarily involving both cerebral hemispheres. The pregnancy was continued with close fetal and maternal surveillance. The patient underwent a repeat cesarean delivery in her 37th week. The infant had a 1 month neonatal intensive care unit stay with care rendered by a multiple disciplinary team of pediatric subspecialists. The postnatal course was complicated by global hypotonia, poor feeding, delayed development and ultimately required anticonvulsants for recurrent seizures. He died at the age of 9 months from aspiration during a seizure.Discussion Although the maternal mortality from DKA has declined, DKA still confers significant neurological fetal morbidity to its survivors.
Keywords: diabetic pregnancy; diabetic ketoacidosis; encephalomalacia